2018
DOI: 10.31533/pubvet.v12n11a210.1-8
|View full text |Cite
|
Sign up to set email alerts
|

Induction of heifers for artificial insemination protocol at fixed time: Review

Abstract: The present work aimed to describe some important concepts regarding the reproductive physiology of pharmacological control of the estrous cycle, presenting different protocols for IATF. IATF has become one of the leading reproductive biotechnologies of economic importance in cattle production globally. The different drugs currently available on the market allow synchronization of the estrous cycle in heifers with the aim of maximizing reproductive rates. In the current literature, numerous protocols are cited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Additionally, the application of E2 prevents smaller follicles from developing, interrupting the rise in follicle-stimulating hormone (FSH) concentration. Thus, the two waves of gonadotropins signaling the start of follicular growth are interrupted; this synchronization is referred to as D0, and after 4 days, the emergence of a new follicular wave can be observed (Oliveira et al, 2018).…”
Section: Fixed-time Artificial Inseminationmentioning
confidence: 99%
“…Additionally, the application of E2 prevents smaller follicles from developing, interrupting the rise in follicle-stimulating hormone (FSH) concentration. Thus, the two waves of gonadotropins signaling the start of follicular growth are interrupted; this synchronization is referred to as D0, and after 4 days, the emergence of a new follicular wave can be observed (Oliveira et al, 2018).…”
Section: Fixed-time Artificial Inseminationmentioning
confidence: 99%
“…Effect of estrogens, category, and CL on D0 was found for DDF on D8.5, category and CL on D0 for DDF on D10 and none influence in the results of pregnancy was found in dominant follicle growth rate from D8.5 to D10. Oliveira, et al, (2018) reported that females that have CL at the beginning of the breeding season have higher pregnancy rates compared to acyclic females.…”
Section: Discussionmentioning
confidence: 99%